Legal Certainty of Establishment of Buildings in a City Based on Law Number 28 of 2002 Concerning Buildings - Mukminati, Andan Hafsari; Maharani, Andina Elok Puri (International Journal of Sustainability in Research, 2024)
Regional planning is closely related to the use of places in a region, so important regional planning is expected to help the surrounding region in developing its territory. Regarding licensing, when construction or development is carried out, licensing is of course one of the things that accompanies the activity. In this work, the author uses the Building Construction Permit (PBG) form, especially in the scope of business permits in the city of Surabaya as the research object. Building Construction Approval (PBG) is the latest innovation from the previous form of permit, namely Building Construction Permit (IMB). Using normative legal research methods, the author analyzes the form of legal certainty applied to the issuance of Building Construction Permits (PBG) in the City of Surabaya to conclude in the form of the results of this legal certainty, namely a form of protection and law coercion.